Climate smart Agriculture Interventions in Selected Agricultural Growth Program-II Districts of Harari Region and Dire Dawa Administration: Double Cropping Practices - Ibsa Aliyi Usmane; Abdulaziz Teha Umer; Nasir Siraj; Oromiya Magersa; Badaso Urgesa; Tashoma Urge (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Climate smart technology intervention in production and productivity enhancement of agriculture sector for small holder farmers' livelihood improvement is indispensable options. Taking this in consideration the double cropping practice research activity was undertaken with objectives of evaluate the productivity and profitability of double cropping practice technology under farmers condition, build farmers' knowledge and skill of different crop combination production and management practice and strengthen stakeholders linkages and collaboration among stakeholders. A total of fifteen (15) trial and follower farmers were selected and organized as form of Farmers Research Groups. Improved varieties of common bean (KATB-1 and Batu) and sorghum (Melkam and Local) were replicated on the plot of 10mx10m. The yield performance of the improved varieties (Batu, KATB-1, Melkam and Local sorghum) were 12.13, 13.43, 31.91 and 26.57qt/ha at Sofi, and 12.13, 13.66, 31.96 and 26.47qt/ha at Wahil, respectively. The double cropping practices preferred as it diversify the crop, more yield obtained, and shorter crop cycle, better to cope up the dry spell, efficient use of land, reduce risks of striga and reduce risk of bird infestation. Moreover, based on the obtained result, Batu, KATB-1 and Melkam combination preferred by farmers since they could able to harvest twice within single season. From knowledge point of view the mean score for knowledge test before intervention and after intervention is 4.47 and 7.37 respectively. The result of paired-sample t-test indicates a significant difference between the mean score for knowledge test before intervention and after intervention at 1% significant level. This implies an improvement of farmers' knowledge regarding the improved sorghum and Haricot-bean varieties as double cropping technologies due to technological intervention. Therefore, it is batter to be promoted and scale-up on wider area and reach large number of farmers.